2023
DOI: 10.3390/ijms24108659
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Opportunities in Using Disulfides, Thiosulfinates, and Thiosulfonates as Antibacterials

Lindsay Blume,
Timothy E. Long,
Edward Turos

Abstract: Sulfur-containing molecules have a long history of bioactivity, especially as antibacterial agents in the fight against infectious pathogens. Organosulfur compounds from natural products have been used to treat infections throughout history. Many commercially available antibiotics also have sulfur-based moieties in their structural backbones. In the following review, we summarize sulfur-containing antibacterial compounds, focusing on disulfides, thiosulfinates, and thiosulfonates, and opportunities for future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Among the OSCs of the Allium genus are the thiosulfonates, generated as secondary metabolites by alliinase [ 11 ]. Some of these thiosulfonates have high antioxidant and antibacterial properties demonstrated in a multitude of in vitro and in vivo studies [ 12 , 13 , 14 , 15 , 16 ]. Yin et al [ 17 ] suggested that incorporating OSCs into food systems through exogenous addition could be a viable and advantageous approach for antioxidant protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the OSCs of the Allium genus are the thiosulfonates, generated as secondary metabolites by alliinase [ 11 ]. Some of these thiosulfonates have high antioxidant and antibacterial properties demonstrated in a multitude of in vitro and in vivo studies [ 12 , 13 , 14 , 15 , 16 ]. Yin et al [ 17 ] suggested that incorporating OSCs into food systems through exogenous addition could be a viable and advantageous approach for antioxidant protection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to complete the safety assessment, a two-generation reproductive toxicity study in mice fed with PTSO was performed for the first time. This study was conducted according to the OECD Guideline 416 [ 14 ]. Male and female CD1 mice were exposed to three dose levels of PTSO to investigate its potential toxics effects on two generations, focusing on F1 generation, and taking into account fertility and endocrine endpoints.…”
Section: Introductionmentioning
confidence: 99%